Perbandingan Antara SQLite, Room, dan RBDLiTe Dalam Pembuatan Basis Data pada Aplikasi Android - Raden Bagus Dimas Putra; Eko Setia Budi; Abdul Rahman Kadafi (STMIK Budi Darma, 2020)
Android is one of the largest mobile operating system platforms today. Amid the ever-increasing needs of users, Android programmers are still lacking to meet the current market needs. One of the problems that causes this is the difficulty of creating an internal database, so many people give up to learn to make Android applications. Android's internal database is hard to create because the entire data structure on that database should be built with the query executed in the created program code. Some of the common internal databases currently used are SQLiTe and Room. Both databases are quite difficult to learn where SQLite should build everything from scratch while Room should study the structure and systematics of of the library. Therefore, in this article, the author proposes library and template named